Motivation of nursing undergraduate program entrants: A scoping review protocol. - Leonila Santos de Almeida Sasso; Ana Caroline Dos Santos Costa; Ana Maria Rita Pedroso Vilela Torres de Carvalho Engel; Emília Batista Mourão Tiol; Fabrício Renato Teixeira Valença; Natalia Almeida de Arnaldo Silva Rodrigues Castro; João Daniel de Souza Menezes; Cíntia Canato Martins; Carlos Dario da Silva Costa; Maria Aurélia da Silveira Assoni; William Donegá Martinez; Patrícia da Silva Fucuta; et al. (PLoS ONE)
Motivation is of great importance in the teaching-learning process, because motivated students seek out opportunities and show interest and enthusiasm in carrying out their tasks. The objective of this review is to identify and present the information available in the literature on the status quo of motivation among nursing program entrants. This is a qualitative scoping review study, a type of literature review designed to map out and find evidence to address a specific research objective, following the Joanna Briggs Institute methodology. The objective was outlined using the PCC (Population, Concept, Context) acronym. The protocol was developed and registered on the Open Science Framework (OSF) platform under DOI 10.17605/OSF.IO/EJNGY. The search strategy and database selection were defined by a library and information science professional together with the authors. The search will be carried out in the following databases: Cumulative Index to Nursing and Allied Health Literature, Literatura Latino Americana e do Caribe em Ciências da Saúde, Lilacs Esp, National Library of Medicine (PubMed), ScienceDirect, Scopus, and the Web of Science platform. The researchers will meet to discuss discrepancies and make decisions using a consensus model, and a third researcher will be tasked with independently resolving any conflicts. Data extraction will involve two independent researchers reviewing each article. Documents such as original articles; theoretical studies; experience reports; clinical study articles; case studies; normative, integrative, and systematic reviews; meta-analyses; meta-syntheses; monographs; theses; and dissertations in English, Portuguese, and Spanish from 2017 to 2023 were included. The results will be presented in tabular and/or diagrammatic format, along with a narrative summary.